THE ANALYSIS OF TEACHER TALK AND THE CHARACTERISTIC OF CLASSROOM INTERACTION IN ENGLISH AS A FOREIGN LANGUAGE CLASSROOM - Dina Septryana Putri (Journal of English and Education, 2015)
The study entitled “The Analysis of Teacher Talk and the Characteristic of Classroom Interaction in English as a Foreign Language Classroom” has objectives to find the type of teacher talk and characteristic of classroom interaction in EFL class of a vocational school in Bandung based on Flanders’ Interaction Analysis Categories that consists of indirect and direct influence of teacher, students’ initiation and responds, and silent moment. This research employed observation sheet, questionnaire, and video recording in order to reach the objectives. By using observation sheet, it was discovered that all categories of teacher talk existed in the classroom. However, asking questions and lecturing were the dominant ones. Students’ perception that were gained by making use of questionnaire supported the finding of the categories of teacher talk in which students perceived that their teacher was more likely to influence them indirectly by asking many questions to involve them in the interaction. Then, this teacher talk type was in line with the characteristic of classroom interaction identified by using video recording which was discovered to be content cross. This kind of interaction indicated that teacher relied hard on asking and lecturing the students.